Hemostatic Parameters in Newborn - II. Sequential Study During the First Four Weeks of Life - Kolindewala, J K; Dube, B; Bhargava, V; Dube, R K; Kota, V L N; Das, B K (Thrombosis and Haemostasis, 1986)
A sequential study of kaolin cephalin clotting time (KCCT), prothrombin time (PT), thrombin time (TT), plasma fibrinogen and serum FDP was conducted during the first four weeks of life on term and preterm babies. A “physiological dip” of PT and TT was noted inappropriate for gestational age (AGA) babies both term and preterm; in case of KCCT, the dip was significant in term AGA babies only. At the end of four weeks, PT and TT had moderately improved in term babies but showed little improvement in preterm ones; KCCT reached almost an adult value in all babies except in preterm AGA and term LGA (large for gestational age) ones. Plasma fibrinogen showed no “physiological dip” and reached adult level in two to four weeks. Serum FDP levels were appreciably raised in preterm AGA babies only at birth and there too normalised by 72 h.
Keywords: Neonate; Preterm; Term; SGA; AGA; LGA; Blood coagulation; Hemostasis